Strategi Bertahan Hidup Pengemudi Ojek Online Selama Masa Pandemi Covid-19 di Kota Matsum II Medan - Ariska Azhar; Bengkel Bengkel (Jurnal Studi Ilmu Sosial dan Politik, 2022)
Purpose: This study aims to determine the survival strategies used by ojek online drivers in Matsum II City, Medan during the COVID-19 pandemic. Methodology/approach: This research is a survey research with data collection techniques carried out through observation and in-depth interviews. The sample of this research is online motorcycle taxi drivers in Matsum II City Medan. Results/findings: The results of this study found that online motorcycle taxi drivers in the City of Matsum II Medan use active and passive strategies to survive. The active strategy is carried out with double work. In addition to the passive strategy is to save on daily expenses, especially expenses for needs that are not too important. Limitations: This research is limited to the process of collecting data through interviews which are sometimes not in-depth, because some drivers have difficulty communicating. Contribution: This research is expected to be able to contribute in the field of social science regarding survival strategies carried out by ojek online drivers during the Covid-19 pandemic, as well as being a reference for future authors with a focus on survival strategy studies.